European migrant crisis as a segment of the media agenda in Serbian daily newspapers 2015–2020 - Jevtović, Zoran B.; Bajić, Predrag Đ. (Sociološki pregled, 2022)
The research is aimed at showing the ways in which the media image of the European migrant crisis changed on the front pages of Serbia’s dailies from 2015, when this crisis hit the headlines, until the end of 2020, when it subdued substantially, but continued to find its place occasionally on the front pages. The lack of discussion in public space is observed, so that the tone of the narrative is adjusted to the opinion of the ruling structures. Simplification and stigmatization are specific for tabloids that, under the guise of market competition, resort to sensationalism, problematic news and unconfirmed information, while serious press rather tends to promote the human aspect of the crisis, with a more profound analysis of the context. Since spring 2016, the writing about this topic has become less intense, but also a slight qualitative change in the narratives in which the emphasis is laid on the possibility of migrants’ longer stay in this territory as well. Moreover, with time, there is a significant shift in the context from the humanitarian towards the security aspect.
Keywords: migrants; refugees; asylum seekers; the Balkan route; media image